1988
DOI: 10.1177/000331978803900907
|View full text |Cite
|
Sign up to set email alerts
|

Surgonomics: The Costs of Ruptured Abdominal Aortic Aneurysm

Abstract: Surgical care costs continue to rise at a rate greater than overall U.S. economic growth. Government and industry have vowed to slow the growth of health care spending. Prospective payment systems using the Diagnostic Related Group (DRG) mechanism are being phased in for payment of in-patient hospital care. One expected effect of the DRG payment scheme is a more careful financial analysis of the components of surgical care. The purposes of this study were to examine a vascular procedure, ruptured abdominal aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In recent years, endoscopic therapy has gradually become the primary prophylaxis against bleeding of gastric varices. Endoscopic variceal ligation [ 20 ] and endoscopic sclerotherapy [ 21 ] have been widely used in variceal bleeding. However, both of them are prone to rebleeding and recurrence after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, endoscopic therapy has gradually become the primary prophylaxis against bleeding of gastric varices. Endoscopic variceal ligation [ 20 ] and endoscopic sclerotherapy [ 21 ] have been widely used in variceal bleeding. However, both of them are prone to rebleeding and recurrence after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This observation notwithstanding, the current study supports an aggressive surgical approach toward the elderly patient who presents with an rAAA. 22 Although the mortality rate is higher than that in younger patients, survival occurs frequently. Furthermore, recent studies have demonstrated that elderly survivors of rAAA repair are just as likely to resume their premorbid quality of life as are younger rAAA survivors or elderly patients who undergo elective aneurysm surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, 39,000 AAA repairs were performed in the United States for a total health cost of approximately $933 million ($23,931 per patient). 2,3 AAAs are always associated with significant aortic atherosclerosis and because of this association have been classically described as random variants of atherosclerosis that occur at a weakened site in the arterial wall. The aneurysm is , thought to grow according to Laplace's law until eventually it ruptures.…”
mentioning
confidence: 99%